Corporate turnaround failure: is the proper diagnosis transgenerational response?. Issue 4 (20th April 2020) - Oliver, John J.
Abstract : Purpose: This paper provides further evidence on a thought-provoking idea, Transgenerational Response, which was previously presented in this journal. It argues that a corporate crisis event can create dysfunctional adaptive attitudes and behaviors which subsequently become embedded in the corporate culture of a firm to the detriment of its long-term performance. Design/methodology/approach: A multi-method approach consisting of longitudinal content analysis of innovation and risk words in corporate annual reports and quantitative financial analysis divided the data into 'what happened before the crisis event' and 'what happen after the crisis event'. Findings: Case studies for AIG and Yahoo illustrate how a crisis event produced chronic financial performance and adaptive cultural responses that include a fall in innovation and an increased emphasis on risk in the years following the incident. Research limitations/implications: This paper does not make claims of generalisability of the findings. However, it does provide a platform for future researchers to develop this line of reasoning and perhaps extend it to consider why some organizations demonstrate greater levels of resilience when faced with a crisis. Practical implications: Identifying a Transgenerational Response means that business leaders can identify how a historic event has affected the performance and cultural dynamics of their firm over time. As such, it will be easier to manage the inherited cultural attitudes and behaviours that have combined to consolidate a firms chronic underperformance. Originality/value: This highly original, evidence-based idea, has the potential to reshape our current understanding of corporate turnarounds, CEO turnover, underperformance and adaptive cultural change.